Original paperMECHANICAL ANALYSIS OF THE ROUNDHOUSE KICK ACCORDING TO HEIGHT AND DISTANCE IN TAEKWONDO - Estevan, I.; Falco, C. (Biology of Sport, 2013)
Competition regulation in taekwondo has experienced several changes during the last few years, for example, kicks to the head score more points than kicks to the chest. In addition, some external factors such as the height of target and execution distance seem to affect the kick performance. The aim of this study was to analyse selected biomechanical parameters (impact force, reaction time, and execution time) according to the height and execution distance in two different male groups (experts (n = 12) and novices (n = 21)). Athletes kicked twice from every execution distance (short, normal and long) and towards two different heights of target (chest and head) in a random order. Novices kicked to the head with a longer reaction time than to the chest (p < 0.05) but experts were able to kick with similar performance for both heights. From short and normal distances experts kicked with similar performance; whereas from the normal distance novices had longer reaction and execution time than from the short distance (p < 0.05). In conclusion, in counterattacking situations, experts should perform the roundhouse kick to the head instead of to the chest, because it produces better scores with similar performance; whereas novice athletes should avoid kicking to the head because they are not able to kick with similar performance. Moreover, it is recommended that during counterattacks higher-level taekwondo athletes should intend to kick from normal distances.